A 75-Year-Old Female with Hemoptysis and Recurrent Respiratory Infections - Baker, Mary S. (Hindawi Publishing Corporation, 2013)
This paper describes the case of a 75-year-old female who presented with significant hemoptysis over a 7–10 day period. She had a history of a left lower lobectomy 10 years prior for a “lung abscess.” She subsequently had multiple episodes of cough, fevers, and possible pneumonia treated with multiple courses of Amoxicillin and Amoxicillin/Clavulanate. Review of her chest CT upon presentation to the hospital showed a large necrotic lingular infiltrate, which had been progressively increasing in size over at least one year. Bronchoscopy showed a yellowish, soft round body in the superior lingular subsegment. Endobronchial and transbronchial biopsies showed actinomyces species. This is a very interesting case of indolent actinomycosis which we suspect had a very slow progressive course secondary to the multiple courses of antibiotics that the patient was treated with.